Interleukin‐33 contributes to disease severity in Dengue virus infection in mice. Issue 4 (10th September 2018) - Marques, Rafael E.; Besnard, Anne‐Gaëlle; Maillet, Isabelle; Fagundes, Caio T.; Souza, Danielle G.; Ryffel, Bernhard; Teixeira, Mauro M.; Liew, Foo Y.; Guabiraba, Rodrigo
Summary: The excessive inflammation often present in patients with severe dengue infection is considered both a hallmark of disease and a target for potential treatments. Interleukin‐33 (IL‐33) is a pleiotropic cytokine with pro‐inflammatory effects whose role in dengue has not been fully elucidated. We demonstrate that IL‐33 plays a disease‐exacerbating role during experimental dengue infection in immunocompetent mice. Mice infected with dengue virus serotype 2 (DENV2) produced high levels of IL‐33. DENV2‐infected mice treated with recombinant IL‐33 developed markedly more severe disease compared with untreated mice as assessed by mortality, granulocytosis, liver damage and pro‐inflammatory cytokine production. Conversely, ST2 −/− mice (deficient in IL‐33 receptor) infected with DENV2 developed significantly less severe disease compared with wild‐type mice. Furthermore, the increased disease severity and the accompanying pathology induced by IL‐33 during dengue infection were reversed by the simultaneous treatment with a CXCR2 receptor antagonist (DF2156A). Together, these results indicate that IL‐33 plays a disease‐exacerbating role in experimental dengue infection, probably driven by CXCR2‐expressing cells, leading to elevated pro‐inflammatory response‐mediated pathology. Our results also indicate that IL‐33 is a potential therapeutic target for dengue infection. Abstract : Interleukin‐33 (IL‐33) plays a disease‐exacerbating role during experimental dengue infection in immunocompetent mice. Dengue virus serotype 2 (DENV2) ‐infected mice that are deficient in IL‐33 receptor developed significantly less severe disease when compared with wild‐type mice. IL‐33 leads to an elevated pro‐inflammatory response‐mediated pathology in DENV2 infection, which is likely driven by CXCR2‐expressing cells.